Ablation behavior and thermal protection performance of TaSi2 coating for SiC coated carbon/carbon composites. Issue 3 (15th February 2019) - Liu, Fei; Li, Hejun; Gu, Shengyue; Yao, Xiyuan; Fu, Qiangang
Abstract: For extending application of TaSi2 in complex coating system, the ablation behavior and thermal protection performance of TaSi2 coating is studied to evaluate its potential applications for anti-ablation protection of C/C composites. TaSi2 coating is prepared by supersonic atmospheric plasma spraying (SAPS) on the surface of SiC coated carbon/carbon (C/C) composites. Phase variation and microstructure are characterized by XRD and SEM, respectively. During the ablation process, the coating is quickly oxidized to SiO2 and Ta2 O5 accompanied by a lot of heat consumption. The linear and mass ablation rates are 0.9 µm s −1 and − 0.4 mg s −1 after ablation for 80 s, respectively Results show that the prepared coating possesses optimal ablation performance under the heat flux of 2.4 MW/m 2 . Moreover, the TaSi2 coating and SiC inner coating have good chemical and physical compatibility during the ablation process. Therefore, the excellent performance of TaSi2 coating during the ablation process makes it a candidate for anti-ablation protection for C/C composites.